2003
DOI: 10.1177/014556130308200810
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Guidelines for ENT Medications during Pregnancy

Abstract: Profound physiologic changes occur during pregnancy, and they can alter the pharmacodynamics ofan administered drug. Almost 85 % of women take at least one prescription medication during a pregnancy. Nearly every drug administered to a mother crosses the placenta, and fetal drug levels can reach 50 to 100% ofmaternal serum concentrations. Because many otolaryngologic conditions are associated with pregnancy, it is essential that otolaryngologists who care for gravid patients know which drugs are safe and avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…34 However, corticosteroid therapy is thought to be safe when corticosteroids are used in the third trimester according to Ambro et al's prescribing guidelines. 35 Zeng et al 18 and Zhang 19 also showed that oral prednisone use in pregnant women with SSNHL achieved a satisfactory recovery. There were also no apparent harmful side effects found in the mothers and infants who were followed up for several years.…”
Section: Corticosteroid Therapymentioning
confidence: 97%
“…34 However, corticosteroid therapy is thought to be safe when corticosteroids are used in the third trimester according to Ambro et al's prescribing guidelines. 35 Zeng et al 18 and Zhang 19 also showed that oral prednisone use in pregnant women with SSNHL achieved a satisfactory recovery. There were also no apparent harmful side effects found in the mothers and infants who were followed up for several years.…”
Section: Corticosteroid Therapymentioning
confidence: 97%
“…Rarely, hormonal and hemodynamic shifts during pregnancy result in pathology that requires intervention by an otolaryngologist. Physicians may find the care of pregnant patients intimidating, as the risks posed by common medications and surgical intervention to both the pregnant patient and the developing fetus are poorly understood . As a further complication, risks of interventions to the developing fetus may vary depending on the stage of fetal development .…”
Section: Introductionmentioning
confidence: 99%
“…Physicians may find the care of pregnant patients intimidating, as the risks posed by common medications and surgical intervention to both the pregnant patient and the developing fetus are poorly understood. 1 As a further complication, risks of interventions to the developing fetus may vary depending on the stage of fetal development. 2,3 In this review, we address common otolaryngologic manifestations in the pregnant patient and the safety of routine medications and summarize precautions to take when it is necessary to intervene surgically with a pregnant patient.…”
mentioning
confidence: 99%